Training and Development of the Human Resource in Institutes of Consecrated Life: A Case of Tangaza University College (TUC) and Marist International University College (MIUC) (International Journal of Scientific Research and Management (IJSRM), 2018)
This study focuses on training and development of the human resource in institutes of consecrated life; a case of Tangaza University College (TUC) and Marist International University College (MIUC). Institutions and organizations exist to achieve certain goals and objectives. These goals and objectives can be successfully achieved through the human resource. However, the human resource must have the right skills and continuously polish their skills. The human resource that is the centre of interest in this study is the consecrated men and women who are members of the institutes of consecrated life in TUC and MIUC and their leadership. Njino (2009) strongly argues that the Church has enormous human resource but at times this resource is underutilized and its abilities and potential are unexploited or unrecognized. This was the motivation and driving factor for this study. The researcher carried out a survey. The specific method employed was descriptive survey design. The target population for the study was all professed members of institutes of consecrated life both men and women with their leadership. The study was developed by integrating interactive shared experiences of men and women religious. These are presented as cases within the different chapters. As a result the researcher only used questionnaires that contained both closed ended and open ended questions in data collection. A total of 242 individual members and 20 members of the different leadership categories of institutes of consecrated life participated in the study. The findings reveal that availability of training policies is dependent on the category of institutes of consecrated life. Majority of the respondents indicated that professional training of members was not a priority for the leadership of the institutes of consecrated life. Work allotment entirely depends on the needs of the individual institute of consecrated life. The researcher recommends that more emphasis is to be put in the training and development of the human resource in institutes of consecrated life. This is because it shall ensure sustainability of the institute.